Morphological Divergence, Reproductive Isolating Mechanism, and Molecular Phylogenetic Relationships Among Indonesia, Malaysia, and Japan Populations of the Fejervarya limnocharis Complex (Anura, Ranidae) - Djong, T.H.; Matsui, M.; Kuramoto, M.; Belabut, Daicus Martin; Yong, Hoi Sen; Nishioka, M.; Sumida, M. (Zoological Society of Japan, 2007)
In order to elucidate the taxonomic status of the Fejervarya limnocharis complex relative to Malaysia and Japan populations, morphological observations and molecular phylogenetic analysis were carried out using three populations from Indonesia (type locality), Malaysia, and Japan. In addition, we conducted histological and spermatogenic observations using hybrids among these populations. Principal component and cluster analyses demonstrated that these populations could be clearly separated from one another. Abnormal testes were found in the hybrids between the Japan and Indonesia populations and between the Japan and Malaysia populations, but testes of the controls and hybrids between the Malaysia and Indonesia populations were quite normal. The mean number of univalents per cell was 5.42, 4.58, and 0.20 in hybrids between the Indonesia and Japan populations, Malaysia and Japan populations, and Indonesia and Malaysia populations, respectively. Sequence divergences in 16S rRNA and Cyt b genes were 0–0.4% (x̄=0.2%) and 0.3–1.5% (x̄=1.0%), respectively, between the Malaysia and Indonesia populations, and 2.4–2.6% (x̄=2.5%) and 11.0–12.0% (x̄=11.5%) between the Japan population and F. limnocharis complex, including the Malaysia and Indonesia populations and F. multistriata from China. This study indicated that the Malaysia population and F. multistriata from China should be designated as a subspecies of topotypic F. limnocharis, and that the Japan population should be regarded as a distinct species.